Administration of a High-Dose Erythropoietin-Stimulating Agent in Hemodialysis Patients is Associated with Late Arteriovenous Fistula Failure - Jeong, Hye Yun (Yonsei Med J, 2017)
PURPOSE: Investigating the risk of vascular access failure is critical for maintenance hemodialysis (MHD) patients. Erythropoietin stimulating agents (ESA) typically used for anemia of chronic kidney disease (CKD) may also stimulate neointimal hyperplasia, which is the most important factor in late arteriovenous fistula (AVF) failure. The aim of this study was to investigate whether ESA treatment is associated with late AVF failure. MATERIALS AND METHODS: The late AVF failure group comprised 51 patients who underwent percutaneous intervention or surgery for fistula revision after successful use for at least three months. There were 51 controls whose AVF had been patent for at least 24 months. RESULTS: The mean time from the first cannulation to late loss of AVF patency was 8.4±4.2 months. The average weekly dose of ESA was significantly higher in patients with AVF failure (4782.2±2360.5 IU/mL/wk vs. 7161.8±2775.2 IU/mL/wk, p<0.001). The only independent predictor of late AVF failure in multivariate analysis was high average ESA dose (odds ratio=1.015, 95% confidence interval=1.002–1.028, p=0.022). CONCLUSION: Patients with late AVF patency loss exhibit an association with a higher dose of ESA, although causality is unproven. Further study to elucidate potential mechanisms is warranted.